Challenging Topics in Neuroanesthesia and Neurocritical Care - Khan, Zahid Hussain (Springer International Publishing : Imprint: Springer, 2017)
This book focuses on controversial issues in neuroanesthesia and neurocritical care that in general have been subjected to insufficient professional scrutiny. The book is in three parts, the first of which is devoted to topics relating to traumatic brain and spinal cord injury, such as brain tissue oxygenation, the role of biomarkers, and diagnosis of brain death. Aspects of airway and pain management are then addressed, covering, for example, airway management in an emergency setting, airway evaluation in the edentulous patient, and pain management in neurosurgery and after craniotomy. The final part of the book considers a wide range of other challenging subjects in the field of neuroanesthesia and neurocritical care. Throughout, much information is provided on the latest, state of the art management. The authors are acknowledged experts in the issues they discuss, and the book will be of interest for graduate and undergraduate students, residents, neuroanesthetists, neurointensivists, emergency medicine residents and specialists, fellows in neurocritical care and all those directly involved in the perioperative care of patients with head and neck pathology.
Keywords: Medicine.; Anesthesiology.; Emergency medicine.; Neurosurgery.; elektronické knihy; electronic books